Clinical value of genetic analysis in prenatal diagnosis of short femur. Issue 11 (30th September 2019) - Liu, Jialiu; Huang, Linhuan; He, Zhiming; Lin, Shaobin; Wang, Ye; Luo, Yanmin
Abstract: Background: Fetal femur length (FL) is an important biometric index in prenatal screening. The etiology of short femur is diverse, with some pathogenic causes leading to adverse outcomes. To improve the accuracy and practicability of diagnosis, we investigated the value of genetic analysis in prenatal diagnosis of short femur. Methods: We examined chromosomal microarray analysis (CMA) (64 fetuses) and karyotyping (59 fetuses) data retrospectively for short femur without fetal growth restriction (FGR). Genetic testing was conducted for 15 fetuses. Results: Karyotyping and CMA detected chromosomal aberrations at rates of 13.6% and 27.2%, respectively. Among fetuses with other abnormalities, detection rates were 21.0% higher with CMA than karyotyping. CMA identified chromosomal abnormalities in 36.4% of cases with a FL 2–4 standard deviations (SDs) below the gestational age (GA) mean. Abnormality detection by CMA reached 38.5% in the second trimester. Duplication of 12p, 16p13.1 deletion, and uniparental disomy 16 were identified by CMA in three cases of short femur. Gene sequencing detected clinically notable mutations in 12/15 fetuses, among which 9/12 fetuses had FLs >4 SDs below the GA mean. Conclusions: CMA yielded a higher detection value than karyotyping in fetuses with other abnormalities or a FL 2–4 SDs below the GA mean during the second trimester. Gene sequencing should be performed when FL is >4 SDs below the mean. Abstract : This article retrospectively investigated the genetic analysis of prenatal diagnosis of fetal short femur. We found CMA yielded a higher detection value than karyotyping in fetuses with other abnormalities or a FL 2–4 SDs below the GA mean during the second trimester. We highlight the significance of performing gene sequencing on fetuses with extremely short femur.